Prioritizing environmental justice in the port hinterland policy: Case of Busan New Port - Lee, Youhyun; Song, Hyojin; Jeong, Suhyun (Research in Transportation Business and Management, 2021)
The greenhouse gases and ultrafine dust generated by ports degrade the environmental quality of life of local residents in port hinterlands. Nevertheless, the hinterland has rarely been considered a major target in maritime policy. Our study aims to suggest a practical policy direction for designing a sustainable port hinterland policy from an environmental justice perspective. To explore the possibilities, we used the analytic hierarchy process methodology to examine 20 policymakers who are involved in the port policymaking process and conducted additional interviews. The results show that procedural justice should prioritize the pursuit of sustainable port hinterlands. More precisely, the most urgent task is the institutionalized participation of residents in the hinterland; constructing eco-friendly infrastructure is scored as the next-most important task. Our study highlights the importance of focusing on the hinterland where local residents encounter environmental injustice, suggesting possible and practical policy implications.
Keywords: AHP; Busan New Port; Environmental justice; Green port hinterland